Spatial Autocorrelation of Tuberculosis Cases in Central Java Province in 2022 - Saini, Izzatul Mardiah; Eryando, Tris (UI Scholars Hub, 2024)
Tuberculosis still becomes a health problem both in the world and in Indonesia. Central Java is The third highest province of tuberculosis in Indonesia. Spatial analysis is an essential tool for evaluating the tuberculosis distribution pattern according to geographic location. This research aims to determine tuberculosis hotspot areas and discover whether there is a spatial correlation between districts/cities in Central Java based on tuberculosis cases using the spatial autocorrelation method through the Moran Index and Local Indicators of Spatial Associations (LISA). Secondary data in the form of the aggregate number of all tuberculosis cases in 2022 was collected from the Indonesian Central Statistics Agency published in Central Java in Figures 2023. Analysis was carried out using ArcViw Gis 3.3 and GeoDa software and the unit of analysis of the study is districts/cities. The results of the research show that there is negative spatial autocorrelation with no spatial autocorrelation. This result means tuberculosis cases in one adjacent district/city in Central Java Province have different values and tend to spread. The area that will become a tuberculosis hotspot in Central Java in 2022 is Tegal Regency. The health intervention is suggested to be performed in tuberculosis hotspot areas to reduce tuberculosis cases in Central Java